Factors determining the development of SMEs in Poland in 2015-2020 = Czynniki determinujące rozwój przedsiębiorstw z sektora MŚP w Polsce w latach 2015-2020 - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
The main objective of the article is an attempt to identify factors/determinants conditioning the development of enterprises in Poland in recent years. The author will also try to indicate the dominant behaviours related to the notion of entrepreneurship among the owners of the enterprises under study.
Keywords: entrepreneurship; entrepreneurship development; determinants; business development factors; przedsiębiorczość; rozwój przedsiębiorczości; determinanty; czynniki rozwoju przedsiębiorstwa